(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This paper investigates the public perception of government poverty reduction policies and participation in community development programmes in Yakurr Local Government Area of Cross River State, Nigeria. Using a mixed-methods approach, including surveys and focus group discussions, the study provides empirical insights into how these policies are perceived and the extent of community involvement. Findings reveal a complex relationship between government efforts and public response, highlighting both support and significant concerns regarding policy implementation, transparency, and effectiveness. Additionally, participation in community development programmes is influenced by factors such as awareness of the programme (55%), perceived effectiveness (40%), and trust in government (30%). The article concludes with recommendations for improving policy design and community engagement to enhance the efficacy of poverty reduction efforts in Yakurr Local Government Area.